Design and analysis of VBF and EEVBF routing protocols for energy efficient underwater communication - Vijayalakshmi, P; Jacintha.T, Aruna; Rajendran, V (International Journal of Engineering and Technology, 2018)
Major constrain in Acoustic communication network is the consumption of energy by senor nodes. The need to regulate the energy con-sumption of senor nodes relay mainly on underwater applications like disaster prevention, tsunami warning and other environmental moni-toring, where the sensor need to transmit the sensed data constantly to the control station for critical analysis. This paper mainly focuses in designing a routing protocol that can challenge a better life expectancy of underwater sensor nodes. From the broader area of research in UWSN, VBF routing protocol gives a promising performance in term of increase in data throughput, PDR and energy consumption. Hence an energy efficient vector based forwarding protocol (EEVBF) is designed which can efficiently regulates the energy consumption when compared to VBF. Based on simulation results, the performance analysis of data throughput, packet delivery ratio, and energy consumed using aquasim network simulators.Â Â